2021
DOI: 10.1002/jgc4.1384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lived experience on risk perception among women who received a breast cancer polygenic risk score: ‘Another piece of the pie’

Abstract: Polygenic risk scores (PRS) are personalized assessments of disease risk based on the cumulative effect of common low-risk genetic variants. PRS have been shown to accurately predict women's breast cancer risk and are likely to be incorporated into personalized breast cancer risk management programs. However, there are few studies investigating the individual impact of receiving a breast cancer PRS. Existing studies have not demonstrated significant changes in perceived risk or risk management behaviors after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…This is supported by our results which showed that those with an affected first-degree relative were more likely to believe they were at risk of developing glaucoma. Previous studies have shown that risk perception is often influenced by lived experience 32 36 and that PRS may not alter perceived risk in these cases. 32 Interestingly, in this study, individuals with an affected first-degree relative were not more likely to change the current frequency of eye examinations, regardless of whether a test indicated they were at either low or high risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by our results which showed that those with an affected first-degree relative were more likely to believe they were at risk of developing glaucoma. Previous studies have shown that risk perception is often influenced by lived experience 32 36 and that PRS may not alter perceived risk in these cases. 32 Interestingly, in this study, individuals with an affected first-degree relative were not more likely to change the current frequency of eye examinations, regardless of whether a test indicated they were at either low or high risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that risk perception is often influenced by lived experience 32 36 and that PRS may not alter perceived risk in these cases. 32 Interestingly, in this study, individuals with an affected first-degree relative were not more likely to change the current frequency of eye examinations, regardless of whether a test indicated they were at either low or high risk. However, this cohort was also the one reporting the highest frequency of eye examination and may therefore feel that additional testing is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the negative reactions our research showed were mitigated in other studies by the involement of a healthcare provider in pre-test or post-test counseling. Additionally, prior studies provided targeted PRSs to individuals with a personal or family history of cancer (16)(17)(18)(19)(20)(21) or bipolar disorder (22). It is possible that having a family history may lead to an overestimation of perceived genetic risk, reducing the burden of a PRS.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse reactions and decisional regret have been reported among people who have self-initiated non-PRS related DTC-GT (13)(14)(15). To date, PRS research has mainly focused on contexts where PRSs are provided to individuals with a personal or family history of cancer (16)(17)(18)(19)(20)(21) or bipolar disorder (22). When provided in these settings, PRSs have served as an explanation for people's personal or family history and reduce feelings of self-blame.…”
Section: Introductionmentioning
confidence: 99%
“…The lived experiences of many women with a family history of breast cancer are a primary source of knowledge on how to live with cancer and cancer risk, and greatly influence perceptions of cancer risk and risk management [ 11 , 12 , 13 , 14 , 15 ]. An elevated perception of risk may negatively impact some women leading them to adopt inappropriate risk management strategies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%